37.8k views
3 votes
Multiply

(s - 5)(2s + 7)
(s - 5)(25+7)=(Simplify your answer.)

(SOMEONE PLEASE ANSWER)

Multiply (s - 5)(2s + 7) (s - 5)(25+7)=(Simplify your answer.) (SOMEONE PLEASE ANSWER-example-1
User Nick Shaw
by
4.7k points

2 Answers

2 votes

(s - 5)(2s + 7) =

= 2s² + 7s - 10s - 35 =

= 2s² - 3s - 35

User Hesky
by
5.0k points
2 votes

Answer:

2s² - 3s - 35 {final answer}

Explanation:

Let's find simplest form of equation,

→ (s - 5)(2s + 7)

→ 2s² + 7s - 10s - 35

→ 2s²- 3s - 35

Thus, the answer is 2s²- 3s - 35.

User Bob Ross
by
5.0k points